Impact of Propolis Administration on Osteocrin Expression and Osteoblast-to-Osteoclast Ratio in the Femurs of Rats Fed a High-fat Diet - Widiyanti, Alvira; Tarawan, Vita Murniati; Lubis, Leonardo (Global Medical & Health Communication (GMHC), 2024)
A high-fat diet (HFD) is associated with bone inflammatory processes that can affect bone remodeling balance. Osteocrin produced by periosteal osteoblasts correlates with osteoblast activity, is expressed on osteoblast-derived cells, and is localized in osteoblasts and young osteocytes. Propolis is an antioxidant and anti-inflammatory in bone remodeling by inhibiting proinflammatory factors NF-κB and COX-2, reducing inflammatory suppression of cytokines responsible for osteoclast differentiation and osteoblast apoptosis. The flavonoid content increases the production of nitric oxide and osteoprotegerin, which enhances osteoblastogenesis. This study determined the effect of propolis administration on bone formation and resorption in bone previously damaged by an HFD. This research was conducted in the Animal Laboratory of Postgraduate Building Dipati Ukur and Genetics and Molecular Laboratory Eycman Building, Faculty of Medicine, Universitas Padjadjaran. The research time was from January 2023–May 2024. Male Wistar rats were divided into four groups: normal chow diet (NCD), NCD with propolis administration, HFD, and HFD with propolis administration. The 12-week-old rats were given an HFD for 12 weeks and then treated with propolis at a 300 mg/kgBW dose for nine weeks. The administration of propolis increased the ratio of osteoblasts-osteoclast cells in the femur of the HFD rats but did not affect periosteal osteocrin expression.